2015
DOI: 10.1002/eqe.2575
|View full text |Cite
|
Sign up to set email alerts
|

Average spectral acceleration as an intensity measure for collapse risk assessment

Abstract: Summary This paper investigates the performance of spectral acceleration averaged over a period range (Saavg) as an intensity measure (IM) for estimating the collapse risk of structures subjected to earthquake loading. The performance of Saavg is evaluated using the following criteria: efficiency, sufficiency, the availability or ease of developing probabilistic seismic hazard information in terms of the IM and the variability of collapse risk estimates produced by the IM. Comparisons are also made between Saa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
245
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 265 publications
(254 citation statements)
references
References 26 publications
6
245
0
3
Order By: Relevance
“…A preliminary study of Tsantaki and Adam (2013) showed that for the considered P-delta vulnerable SDOF systems this IM satisfies better the property of efficiency, compared with outcomes of benchmark studies (Adam and Jäger 2012a;Jäger and Adam 2013), where the 5 % damped spectral pseudo-acceleration at the structural period has been used as IM. Eads et al (2015) evaluated the efficiency and sufficiency of a similar IM for collapse prediction using almost 700 moment-resisting frame and shear wall structures. Also, Kazantzi and Vamvatsikos (2015) compared the effectiveness of several IMs based on the geometric mean concept superposing the spectral acceleration read at different logarithmically and linearly equally spaced periods.…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary study of Tsantaki and Adam (2013) showed that for the considered P-delta vulnerable SDOF systems this IM satisfies better the property of efficiency, compared with outcomes of benchmark studies (Adam and Jäger 2012a;Jäger and Adam 2013), where the 5 % damped spectral pseudo-acceleration at the structural period has been used as IM. Eads et al (2015) evaluated the efficiency and sufficiency of a similar IM for collapse prediction using almost 700 moment-resisting frame and shear wall structures. Also, Kazantzi and Vamvatsikos (2015) compared the effectiveness of several IMs based on the geometric mean concept superposing the spectral acceleration read at different logarithmically and linearly equally spaced periods.…”
Section: Introductionmentioning
confidence: 99%
“…A second group of frequently used scalar IMs comprises elastic and inelastic spectral values, such as the spectral acceleration and spectral displacement at the fundamental structural period. Advanced definitions may include the effects of higher modes and period elongation due to inelastic deformation (e.g., Cordova et al 2001;Haselton and Baker 2006;Luco and Cornell 2007;Bianchini et al 2009;Kadas et al 2011;Vamvatsikos and Cornell 2005;Bojórquez and Iervolino 2011;Adam et al 2014;Eads et al 2015). Vector valued IMs (e.g., Vamvatsikos and Cornell 2005;Baker and Cornell 2005) combine several intensity related parameters, and thus, when appropriately defined they capture more comprehensively the intensity of earthquake excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Referring to Eq. (5), it was found that the average spectral acceleration S avg proposed by Eads et al [45,46] provides best estimates of peak and residual SDRs compared to other seismic intensity measures (IM). In particular, the pseudo-acceleration (S a ), peak ground acceleration (PGA), peak ground velocity (PGV), Arias intensity (I a ) [47] were also evaluated.…”
Section: Proposed Empirical Equations For Rapid Earthquake Damage Assmentioning
confidence: 98%
“…In particular, the pseudo-acceleration (S a ), peak ground acceleration (PGA), peak ground velocity (PGV), Arias intensity (I a ) [47] were also evaluated. The S avg is computed as the geometric mean of 5% damped spectral accelerations ranging between 0.2T 1 and 3T 1 with a uniform interval of 0.01s [45,46] (where T 1 is the first-mode natural period of the building under consideration). Similarly, the PGA provides better estimates for PFAs compared to the rest of IMs that were considered.…”
Section: Proposed Empirical Equations For Rapid Earthquake Damage Assmentioning
confidence: 99%